Recycling Cost formation and Profitability of foods and beverages firm: Evidence from Flour Milling Industries of Nigeria Plc (1991-2021) - Madu Ikemefuna; Idris Mohammed Gurin; Madu Rejoice Ezinne (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
Recycling is one of the most viable options to reuse the end of the product in the closed-loop supply chains (CLSC) management. The major focus of this study is to examine the influence of product recycling cost on the profitability of food and beverage firms. This study relied solely on secondary data sourced which was subjected to a mathematical model using regression analysis. It was observed that dependent and the independent variables has a strong positive relationship with r=0.741. The coefficient of determination r2=0.549 shows that 54.9% of the variation in profit can be explained by production cost at 95% level of significant while in the flour mills Nigeria plc, the dependent and the independent variables has a weak positive relationship with r=0.363. The coefficient of determination r2=0.132 shows that 13.2% of the variation in profit can be explained by the production cost at 95% level of significant. Finally in Dangote Nigeria plc, dependent and the independent variables has a weak positive relationship with r=0.174. The coefficient of determination r2=0.030 Shows that 03.0% of the variation in profit can be explained by the production cost at 95% level of significant.